Human Leukocyte Antigen (HLA) DQ2 and DQ8 Haplotypes in Children with Celiac Disease - Shamraiz, Ifnan; Naz, Shaista; Idrees, Saba; Ikram, Farooq; Khan, Husna; Khan, Samina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of human leukocyte antigen-DQ2 and -DQ8 haplotypes in children with celiac disease in a tertiary care hospital.Study Design: Comparative cross-sectional study.Place and Duration of Study: Paediatric Gastroenterology and Hepatology Departments Combined Military Hospital, Rawalpindi Pakistan, from Feb 2022 to Feb 2023.Methodology:  Diagnosed cases of celiac disease, from 1 to 15 years old, were selected as Cases (n=50), and an equal group of normal children of the same age as Control (n=50), were selected. Polymerase chain reaction for Human Leukocyte antigen (Human leukocyte antigen -DQ) genotyping was performed on all children.Results: The most frequently observed haplotype was DQ2, followed by DQ8. Among celiac patients, 94% tested positive for human leukocyte antigen-DQ, with 82% DQ2, 10% DQ8, and 2% DQ2/DQ8 positive. 6% were negative for any HLA-DQ allele, while only 8% were DQ2 positive in the control group. The frequency of human leukocyte antigen -DQ between the two groups was statistically significant (p-value